Myrtus communis L. Extract Ameliorates High Fat Diet Induced Kidney and Bladder Damage by Inhibiting Oxidative Stress and Inflammation - ERTAŞ, BÜŞRA; ŞEN, ALİ; AKAKIN, DİLEK; ERCAN, FERİHA (My University, 2022)
Objective: Obesity is associated with many diseases, including urinary system disorders such as chronic kidney disease and overactive bladder syndrome. Myrtus communis L. (MC) extract has been reported to have antioxidant and anti-inflammatory effects. The aim of this study was to investigate the protective effects of MC extract on high-fat diet (HFD)-induced kidney and bladder damage. Materials and Methods: Wistar albino male rats were divided into three experimental groups: control, HFD and HFD+MC. Experimental groups were fed a standard diet (control group) or HFD (HFD and HFD+MC groups) for 16 weeks. MC extract (100 mg/kg) was administered to the HFD+MC group orally during the last 4 weeks (5 days/week) of the experiment. Highdensity lipoprotein, total cholesterol, triglyceride and leptin levels were measured in blood serum. Tissue malondialdehyde (MDA), glutathione (GSH), 8-hydroxy-2'-deoxyguanosine (8-OHdG) and myeloperoxidase (MPO) levels were evaluated biochemically. Kidney and bladder morphology, NADPH oxidase-2 (NOX-2) and nuclear factor-kappa B (NF-ҡB)-positive and apoptotic cells were evaluated histologically. Results: Lipid profiles altered and leptin levels increased in blood serum. MDA, 8-OHdG and MPO levels increased and GSH level decreased in kidney and bladder in the HFD group. Moreover, degenerated kidney and bladder morphology, increased NOX-2 and NF-ҡB-positive and apoptotic cells were observed in this group. All of these biochemical and histological parameters were ameliorated in the HFD+MC group. Conclusion: HFD-induced obesity causes kidney and bladder damage by oxidative and inflammatory processes. MC extract may reduce oxidative stress and inflammation and play a protective role in obesity-related kidney and bladder damage.
Keywords: Tıp; Histoloji-Embriyoloji; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Histology and Embryology; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Moleküler Biyoloji ve Genetik; TIP, GENEL & DAHİLİ; HÜCRE BİYOLOJİSİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; MEDICINE, GENERAL & INTERNAL; CELL BIOLOGY; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Hücre Biyolojisi; Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Cell Biology; Life Sciences; High fat diet; Myrtus communis L. extract; kidney; bladder; oxidative stress; inflammation